Cyanophyceae Epipelicas de la Marisma “El Cangrejal” en el Estuario de Bahía Blanca (Buenos Aires, Argentina). - Da Rodda, Constanza (2005)
Epipelic Cyanophyceae of the salt marsh «El Cangrejal» in the estuary of Bahía Blanca (Buenos Aires, Argentina). «El Cangrejal», an association of Sarcocornia perennis and Chasmagnathus granulata is situated in the salt marsh of slime-clay tide plains of the estuary of Bahía Blanca (Buenos Aires). In the sediment-water interface microbial mats are mainly constituted by cyanophytes and diatoms. This is a study of the epipelics Cyanophyceae presents in these mats, identifying twenty three taxa corresponding to the Orders Chroococcales (1) and Hormogonales (22). The species are new mention for the study area, an exception are Microcoleus chthonoplastes and Oscillatoria limosa . Symploca hydnoides f. minor is a new record for Argentina.